Perhitungan Harga Pokok Produk Bersama dan Produk Sampingan dengan Penetapan Harga Jual Produksi Tahu dan Ampasnya - Valentina Monoarfa; Nurwinda Pade; Aulia Monika Aswad (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The research project for estimating the cost of goods together and by-products of Ms. Sri's tofu business is discussed in this article. Main products are goods that meet predetermined criteria and are the company's main goal, while side products are goods that are created unavoidably but are not the company's main goal. The aim of this research is to calculate the cost of production of tofu and dregs, and determine the appropriate selling price for these two products. Case studies and literature reviews were the research approaches used in this project. Case studies involve talking to companies and doing research, while literature studies involve looking through books and other sources of information for relevant information. The research method used is the joint cost method with a full costing method approach.